Effect of progressive muscle relaxation on postoperative pain, fatigue, and vital signs in patients with head and neck cancers: A randomized controlled trial. Issue 7 (July 2022) - Loh, El-Wui; Shih, Huei-Fen; Lin, Chung-Kwei; Huang, Tsai-Wei
Highlights: ● Surgical intervention is the principal treatment strategy for head and neck cancers. ● The extent of required reconstruction is a major factor in postoperative discomfort. ● PMR significantly reduces levels of fatigue, anxiety, and depression with time trend. ● PMR could operate by professional, family, even to patients their self. Abstract: Objective: Surgery for head and neck cancers are associated with significant preoperative stress. We investigated the effects of progressive muscle relaxation (PMR) on postoperative pain, fatigue, and vital signs in patients with head and neck cancers. Methods: All patients were hospitalized and randomly assigned to intervention or usual care groups. A generalized estimating equation was used to evaluate the PMR effects on pain and symptoms across the preoperative day to postoperative day 10. Results: The PMR group displayed significantly lower overall pain and muscle tightness than control group along with the timeline of multiple measurements (p < 0.01). PMR significantly reduces sleep disturbances and levels of fatigue, anxiety, and depression compared with the control group with time trend (p < 0.01). PMR also lowered the respiratory rates and diastolic blood pressure (p < 0.01). Conclusions: PMR can reduce sleep disturbances and levels of pain, fatigue, muscle tightness, anxiety, and depression in patients with head and neck cancer undergoing major surgeries. Future study should focus on improving the effectiveness of the exercise and standardization of the application. Practical implications: progressive muscle relaxation help relieve discomforts in patients with head and neck cancers with minimal costs and efforts.